Programmed cell death in Helicobacter pylori infection and related gastric cancer - Lin, Yukun; Liu, Kunjing; Lu, Fang; Zhai, Changming; Cheng, Fafeng (Frontiers in Cellular and Infection Microbiology, 2024)
Programmed cell death (PCD) plays a crucial role in maintaining the normal structure and function of the digestive tract in the body. Infection with Helicobacter pylori (H. pylori) is an important factor leading to gastric damage, promoting the Correa cascade and accelerating the transition from gastritis to gastric cancer. Recent research has shown that several PCD signaling pathways are abnormally activated during H. pylori infection, and the dysfunction of PCD is thought to contribute to the development of gastric cancer and interfere with treatment. With the deepening of studies on H. pylori infection in terms of PCD, exploring the interaction mechanisms between H. pylori and the body in different PCD pathways may become an important research direction for the future treatment of H. pylori infection and H. pylori-related gastric cancer. In addition, biologically active compounds that can inhibit or induce PCD may serve as key elements for the treatment of this disease. In this review, we briefly describe the process of PCD, discuss the interaction between different PCD signaling pathways and the mechanisms of H. pylori infection or H. pylori-related gastric cancer, and summarize the active molecules that may play a therapeutic role in each PCD pathway during this process, with the expectation of providing a more comprehensive understanding of the role of PCD in H. pylori infection.